Pembelajaran Berbantuan E-Modul untuk Meningkatkan Capaian Pembelajaran Kognitif Fungsi Bagian-bagian Mesin Frais - Nurdiansyah, Fahmi; Khumaedi, Muhammad; Kriswanto, Kriswanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The low achievement of students' cognitive learning outcomes in the material of the function of milling machine parts indicates the need for innovation in learning media that is more interactive and adaptive to the characteristics of vocational high school students. This study aims to evaluate the effectiveness of the use of interactive e-modules in improving student learning outcomes in the subject of Machining Engineering. This study uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type involving two classes of XI Machining Engineering at SMK Negeri 1 Karangawen as the experimental group and the control group. The main instrument is a 20-item multiple-choice test that has been validated using the Content Validity Ratio (CVR) and its reliability tested with the Intraclass Correlation Coefficient (ICC). Data analysis included normality test, homogeneity test, two-tailed t-test on pre-test, one-tailed t-test on post-test, and N-Gain analysis. The results showed that there was no significant difference between the two groups in the pre-test (p = 0.762), but there was a statistically significant difference in the post-test (p < 0.001), with an average value of 81.25 for the experimental group and 72.50 for the control group. The average N-Gain of the experimental group reached 0.5515, higher than that of the control group at 0.3543. These findings indicate that interactive e-modules are effective in improving students' cognitive learning outcomes on conceptual and visual materials. Thus, interactive e-modules are worthy of recommendation as alternative digital learning media in vocational education, especially to strengthen the technical understanding of vocational high school students in accordance with the demands of technological developments and the needs of the industrial world.